Imaging of giant cell tumor of bone - Purohit, Shaligram (Medknow Publications, 2007)
Giant cell tumor (GCT) of bone is a benign but locally aggressive and destructive lesion generally occurring in skeletally mature individuals. Typically involving the epiphysiometaphyseal region of long bones, the most common sites include the distal femur, proximal tibia and distal radius. On radiographs, GCT demonstrates a lytic lesion centered in the epiphysis but involving the metaphysis and extending at least in part to the adjacent articular cortex. Most are eccentric, but become symmetric and centrally located with growth. Most cases show circumscribed borders or so-called geographical destruction with no periosteal reaction unless a pathological fracture is present. There is no mineralized tumor matrix. Giant cell tumor can produce wide-ranging appearances depending on site, complications such as hemorrhage or pathological fracture and after surgical intervention. This review demonstrates a spectrum of these features and describes the imaging characteristics of GCT in conventional radiographs, computerized tomography scans, magnetic resonance imaging, bone scans, positron emission tomography scans and angiography.